2010
DOI: 10.1111/j.1551-2916.2010.03801.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Temperature‐Dependent Ferroelastic Behavior of Hard and Soft Lead Zirconate Titanate Ceramics

Abstract: The ferroelastic properties of a hard acceptor‐doped lead zirconate titanate (PZT) ceramic are investigated between room temperature and 300°C. Comparison with a soft PZT shows that acceptor doping has a stronger influence on mechanically induced domain switching than on switching caused by electric fields. A quantitative analysis of spontaneous and remanent strain and polarization indicates that poling in the soft material is dominated by 180° domain processes, while non‐180° processes dominate the strain beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 41 publications
(100 reference statements)
1
37
0
Order By: Relevance
“…The room temperature coercive stresses lead to the conclusion that there is a threshold value for domain switching at a c/a of 1.045, similar to electrical switching. 29 Coercive stress values for compositions around the threshold c/a ratio were found to be in the range of hard-doped PZT, 39 whereas BF-PT materials with high c/a ratios are almost twice as high as found for hard-doped PZT. The observed coercive stress of the undoped sample matches the value found by Kounga et al 32 It is, however, not fully understood why this behavior is not apparent in the strain and energy dissipation induced by the mechanical loading experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The room temperature coercive stresses lead to the conclusion that there is a threshold value for domain switching at a c/a of 1.045, similar to electrical switching. 29 Coercive stress values for compositions around the threshold c/a ratio were found to be in the range of hard-doped PZT, 39 whereas BF-PT materials with high c/a ratios are almost twice as high as found for hard-doped PZT. The observed coercive stress of the undoped sample matches the value found by Kounga et al 32 It is, however, not fully understood why this behavior is not apparent in the strain and energy dissipation induced by the mechanical loading experiments.…”
Section: Discussionmentioning
confidence: 99%
“…However, the maximum strain e max for these compositions shows an increase with increasing lanthanum content (also at elevated temperature). This is because the maximum strain is the product of multiple competing factors, such as the change in Young's modulus as a function of stress, 38,39,47 as well as both the strain generated during domain switching and the amount of domains that are able to switch. For compositions doped with the highest concentrations of lanthanum it was found that the strain response and the dissipated mechanical energy decreased as a function of lanthanum concentration, despite the assumed increase in domain switching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cao and Evans 5 investigated the stress-strain behaviors for both hard and soft doped PZT, showing that the coercive stress of an acceptor (hard) doped material is larger than that of a donor (soft) doped. Webber et al 9 , followed by others 10,21 , reported the temperature-dependent ferroelastic behavior of PZT ceramics in different poling states. It was shown that a reduction of the spontaneous strain is primarily responsible for a decrease of the mechanical stress-induced remanent strain with increasing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[21] There is, unfortunately, little experimental data available on the influence of mechanical stress on acceptor--doped perovskite ferroelectrics. Previous characterization of the macroscopic electromechanical and stress--strain behavior has shown that uniaxial compressive stress can result in ferroelastic switching [22,23] as well as field--induced phase transitions in polycrystalline PZT. [24] Therefore, the primary aim of this work is to investigate role of stress on donor and acceptor--doped Pb(Zr,Ti)O3 through the characterization of the stress--and temperature--dependent direct piezoelectric response.…”
mentioning
confidence: 99%